2016
DOI: 10.1177/0969733016664979
|View full text |Cite
|
Sign up to set email alerts
|

Ethical climate and missed nursing care in cancer care units

Abstract: Efforts to reduce the influence of instrumental and independence types and fostering caring, law and code, and rules types might decrease missed nursing care. However, more robust evidence is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
57
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 44 publications
8
57
0
6
Order By: Relevance
“…Staff from Italian hospitals identified more episodes of missed higher priority care compared with nurses from the two other countries while Cypriot nurses identified more missed treatment related care. This is consistent with other studies from Cyprus (Vryonides et al., ) that found patient bathing, mouth care and turning patients every 2 hours to be omitted by nurses more frequently.…”
Section: Discussionsupporting
confidence: 92%
“…Staff from Italian hospitals identified more episodes of missed higher priority care compared with nurses from the two other countries while Cypriot nurses identified more missed treatment related care. This is consistent with other studies from Cyprus (Vryonides et al., ) that found patient bathing, mouth care and turning patients every 2 hours to be omitted by nurses more frequently.…”
Section: Discussionsupporting
confidence: 92%
“…This finding can be added to the long list of understaffing's negative consequences; based on the international RN4Cast study, 49% of the nurses in Spain did not have time to educate patients and families (Ausserhofer et al., ) due to understaffing (Aiken et al., ). Similar results have been reported in the literature, with patient education not being considered as a priority by the nurses (Papastavrou, Andreou, & Efstathiou, ; Vryonides et al., ). Although this finding may be consistent over the world (Jones, Hamilton, & Murry, ), with the nurses claiming staff shortage, it seems that the origin of omitting “less visible” tasks needs further investigation.…”
Section: Discussionsupporting
confidence: 88%
“…Systematic reviews of studies referring to the phenomenon (Jones, 2015;Papastavrou et al, 2016) pointed out its negative influence on the job satisfaction of nurses and their intentions to leave the workplace (Jones, 2014 Schubert et al, 2008) contribute to a systematic mapping of the associated factors, or more precisely, predictors of the phenomenon; such as the work environment, patient-nurse ratio, performing non-nursing interventions, nursing workload, unexpected increase in the number of patients (or an unplanned increase in care demands, material or resources), communication barriers within the team or in the nurse-patient relationship and, last but not least, ineffective delegation of the tasks (Ausserhofer et al, 2014;Jones, 2015;Kalisch et al, 2009a;2011). According to Jones (2015), the number of nurses along with the work environment characteristics are clearly stronger predictors than the individual characteristics of the nurses (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…According to Papastavrou et al (2016), the third research area focuses on the examination of implicit rationing of nursing care per se, as well as of its implications on the quality of the care and on patient safety (Jones, 2015;Kalisch et al, 2009a;Lucero et al, 2010;Schubert et al, 2008;Sochalski, 2004). Based on the review of research studies in this area, Jones (2015) and Papastavrou et al (2016) have identified the interventions most frequently missed or withheld in the clinical practice due to insufficient resources (personal, time, material, skill-mix). Results in this area point out a high prevalence of these interventions with considerable variability depending on the tool used (its sensitivity and specificity).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation